Tahap-Tahap Penyelesaian Konflik Studi Kasus Suku Hutu dan Tutsi di Rwanda - Adlan Mustafa, Rizal (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The genocide that killed hundreds of thousands of people in Rwanda has its origins in a long history. The country is inhabited by the Hutu tribe, which is the majority there, then the Tutsi, and the smallest tribe is the Twa. They lived side by side and peacefully for hundreds of years until Germany made it part of the country’s province in 1895. Conditions changed when World War I broke out, which resulted in Germany having to lose the territory of Rwanda. It was then determined by the LBB that Rwanda was under the administration of the Belgian state. When controlling Rwanda, Belgium prioritized the Tutsis over the Hutu in all fields because they were considered more advanced, richer, and superior. This discriminatory attitude between tribes resulted in tension between the two parties, which then led to competition to become leaders. This tribal sentiment ultimately led to a prolonged conflict that ended with a massacre that killed 800,000 people. To measure conflict escalation, this research uses Michael Lund’s (1996) conflict curve theory, which divides conflict into several phases, namely: durable peace, stable peace, unstable peace, crisis, and war. These five phases will be used to measure the escalation of the conflict between the Tutsi and Hutu tribes in Rwanda. This research uses an explanatory-qualitative method by collecting data from various sources. In addition, it is analyzed in such a way as to produce research that is able to interpret the object being studied in depth.